THE LEGALITY OF THE ASSAULT ON TAX AVOIDANCE PRACTICES IN THE PHILIPPINES - Sy, Evelyn Kho (Philippine Management Review; Vol 16 (2009), 2010)
The distinction between tax avoidance and tax evasion is very clear in the academe. Tax books have often defined tax avoidance as an attempt to minimize the payment or altogether eliminate tax liability by lawful means, while tax evasion refers to the elimination or reductions of one's correct and proper tax by fraudulent means. The consequence of each case is also clear. The former is not criminally punishable while the latter is criminally punishable. However, the distinction between the two cases seems to have been blurred by the inconsistent practice of the government in its treatment of the subject matter. Very often, the Bureau of Internal Revenue (BIR) asks for a valid business purpose whenever a taxpayer enters into a transaction which has the effect of reducing tax liability. For instance, when a father sells a parcel of land to his son, the BIR looks into the financial capability of the son to buy the subject land, in order to ensure that the sale was not for the sole purpose of saving on the payment of estate taxes. The taxpayer has to come up with a valid reason for selling his land to his son. An honest answer from the taxpayer that the transaction was for purposes of tax avoidance will not be acceptable to the BIR. The BIR will impose the higher tax rate in its assessment, as well as the corresponding interests and penalties. This situation leads one to wonderwhether tax avoidance is legal or not in the Philippines. This paper aims to show that the attack on tax avoidance transactions in the Philippines has no legal basis. It urges consistency and certainty on the part of the government in its response towards tax avoidance. To eliminate further injustice and inefficiencies, it is imperative that a law be passed to inform the taxpayers as to what constitutes "permissible" and "impermissible" tax avoidance. In the absence of such law, tax avoidance transactions entered into by the taxpayers must be respected.
Keywords: tax avoidance, tax evasion